2017
DOI: 10.15171/jarcm.2017.002
|View full text |Cite
|
Sign up to set email alerts
|

Demographic features of pediatric patients with burn injuries referred to the emergency department of Sina hospital in Tabriz, Iran, in 2014

Abstract: Introduction:The aim of this study was to evaluate the demographic status of children with burn injuries who were referred to the emergency department of the Sina hospital in Tabriz, Iran, in 2014. Methods: Total of 220 pediatric patients with burn injuries, who referred to the emergency department of Sina hospital, were enrolled in this prospective descriptive study. Data such as age, gender, type of injury, location of injury, and severity of burns was collected, and analyzed using SPSS statistical software.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…4,14 Our findings showed that the male to female ratio was 1.09:1 which is in agreement with other studies. 3,10,[15][16][17][18] The hyperactive nature of male babies in comparison to female babies may be one explanation for the study's predominance of male participants.…”
Section: Discussionmentioning
confidence: 99%
“…4,14 Our findings showed that the male to female ratio was 1.09:1 which is in agreement with other studies. 3,10,[15][16][17][18] The hyperactive nature of male babies in comparison to female babies may be one explanation for the study's predominance of male participants.…”
Section: Discussionmentioning
confidence: 99%
“…Burn injury is one of the most important injuries to children (1). Severe burns can cause complications and mortality in children and are the most common cause of death related to injury in children (2).…”
mentioning
confidence: 99%